Understanding multifactorial drivers of child stunting reduction in Exemplar countries: a mixed-methods approach. (10th July 2020) - Akseer, Nadia; Vaivada, Tyler; Rothschild, Oliver; Ho, Kevin; Bhutta, Zulfiqar A
ABSTRACT: Background: Several countries have notably reduced childhood stunting relative to economic growth over the past 15–20 y. The Exemplars in Stunting Reduction project, or " Exemplars, " studies success factors among these countries with a lens toward replicability. Objectives: This paper details the standardized mixed-methods framework for studying determinants of childhood stunting reduction applied in Exemplars studies. Methods: An expert technical advisory group (TAG), criteria for identifying Exemplar countries, evidence-based frameworks, mixed methodologies (quantitative, qualitative, policy, literature review), effective research partnerships, case study process and timeline, and data triangulation and corroboration are presented. Results: Experts in health, nutrition, and evaluation methods were selected at the study outset to provide technical support to all phases of research (TAG). Exemplar countries were selected by the TAG, who considered quantitative data (e.g., annual rates of stunting change compared with economic growth, country population size) and qualitative insights (e.g., logistics of country work, political stability). Experienced country research partners were selected and an inception meeting with stakeholder consultations was held to launch research and garner support. Evidence-based conceptual frameworks underpinned all Exemplars research activities. A systematic review of published peer-reviewed and grey literature was undertaken, along with in-depth policy and program analysis of nutrition-specific and -sensitive investments. Both descriptive and advanced quantitative analysis was undertaken (e.g., equity analyses, difference-in-difference regression, Oaxaca-Blinder decomposition). Qualitative data collection using in-depth interviews and focus groups was conducted with national and community stakeholders (i.e., child care workers and mothers) to understand country experiences. The case study process was iterative, and all research outputs were triangulated to develop the stunting reduction narrative for each country. Findings were shared with country experts for weigh-in and corroboration through dissemination events. Conclusions: Exemplars research uses a mixed-methods framework for studying positive outliers that can be applied across diverse health and development outcomes.